Bioprospecting on invasive plant species to prevent seed dispersal. Issue 1 (December 2017) - Guzzetti, Lorenzo; Galimberti, Andrea; Bruni, Ilaria; Magoni, Chiara; Ferri, Maura; Tassoni, Annalisa; Sangiovanni, Enrico; Dell'Agli, Mario; Labra, Massimo
Absract The most anthropized regions of the world are characterized by an impressive abundance of invasive plants, which alter local biodiversity and ecosystem services. An alternative strategy to manage these species could be based on the exploitation of their fruits in a framework of bioprospecting to obtain high-added value compounds or phytocomplexes that are useful for humans. Here we tested this hypothesis on three invasive plants (Lonicera japonica Thunb., Phytolacca americana L., andPrunus serotina Ehrh.) in the Po plain (northern Italy) which bear fruits that are highly consumed by frugivorous birds and therefore dispersed over large distances. Our biochemical analyses revealed that unripe fruit shows high antioxidant properties due to the presence of several classes of polyphenols, which have a high benchmark value on the market. Fruit collection for phytochemical extraction could really prevent seed dispersal mediated by frugivorous animals and produce economic gains to support local management actions.